Comparative histopathological study of the phrenic nerve from corpses with chronic obstructive pulmonary disease and without this condition: Estudio histopatológico comparativo del nervio frénico proveniente de cadáveres con enfermedad pulmonar obstructiva crónica y sin esta condición - Santos-Santana, Fernanda Mayara (2020)
Introduction: Functional changes resulting from the evolution of chronic obstructive pulmonary disease (COPD) are progressive and irreversible, causing increased diaphragm work due to pulmonary hyperinflation and airway obstruction. Phrenic nerves have promoted innervation of the diaphragm and may have been compromised in COPD condition. Objective: To compare the morphology of the phrenic nerves of the cadavers with COPD and without COPD by optical microscopy. Materials and methods: An exploratory descriptive studio conducted on the Death Verification Service in Alagoas. Pulmonary and phrenic nerve biopsies will be bilaterally taken from the cadavers after a necropsy with the diagnosis of COPD. Tissue samples were fixed and processed by conventional histology for hematoxylin-eosin (HE) histological slides. Biopsies are divided into experimental groups, one composed by patients with COPD and the other with patients without COPD (control - CTR). This classification was realized after the histological analysis, when typical halls of COPD were found. Histological slides were analyzed by optical microscopy by a pathologist, who was able to assess the study. Results: According to the inclusion and exclusion criteria of the study, if it includes 38 cadavers in the initial evaluation, of which 31 are included in the COPD group and 7 in the CTR group. In the analysis of the phrenic nerves, 8 cadavers, 25.8%, of the COPD group had histopathological changes: perineural edema (75%, n=6), nervous atrophy (12.5%, n=1) and perineural eosinophilic infiltrate (12.5%, n=1). The CTR group does not present histopathological alterations of the phrenic nerves. Conclusions: Given the hallmarks of the biopsies performed on the phrenic nerves of the corpses with COPD, we can infer that there is a tendency for nerve alteration, with perineural edema, to be the major modification found.